Pengembangan Modul Praktikum Program Labschool dalam Meningkatkan Kompetensi Profesional Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah - Mahmudah, Masrurotul; Al Ikhwanah, Al Ikhwanah; Makmun, Muh. Ngali Zainal (AR-RIAYAH: Jurnal Pendidikan Dasar, 2021)
Competition for the quality of graduate graduates is both a challenge and an opportunity for every study program, especially the Madrasah Ibtidaiyah Teacher Education study program (PGMI). Self-actualization of the development of job opportunities is important, especially in increasing student competence so that they can graduate and be accepted by stakeholders. This is a supplement to become a conductor in realizing multitalent and professional educators. Based on questionnaires, observations, interviews, and documentation, it was obtained data that the development of the labschool program practicum module in improving the professional competence of the PGMI study program students of the Islamic Religion Institute Ma'arif NU Metro Lampung got a good category. This can be seen from the acquisition of scores of 80% media experts and 78% material experts. This development is expected to be used as a guide for developing student professional competence from the implementation stage to the assessment stage. This program aims to deliver professional and multitalented teaching staff candidates. Thus PGMI graduates are ready to compete in the world of work and can be accepted by graduate users well